Initial Experience with Robot-Assisted Hiatal Hernioplasty: A Case Series - González, Claudia Viviana Jaimes; Hanssen, Andrés; Alvarado, Gonzalo Andrés Domínguez; Rodríguez, Mariana Lucía López (British Journal of Healthcare and Medical Research, 2026)
Introduction: Hiatal hernia is a common pathology whose prevalence increases with age and obesity. Although laparoscopy has been the standard in its surgical treatment, the robotic approach has emerged as a promising alternative, offering greater precision, better ergonomics, and three-dimensional visualization. This study aims to present our initial experience with robot-assisted hiatal hernioplasty through a specific surgical technique and the analysis of a series of clinical cases operated with this approach. Clinical Cases: Four patients with symptomatic hiatal hernias refractory to medical treatment were operated on. All procedures were performed using Nissen-type fundoplication technique, utilizing three robotic arms. Surgical time ranged between 127 and 224 minutes, with no intraoperative or postoperative complications. All patients had good tolerance to the postoperative nutritional plan, adequate reflux control, and hospital discharge between 24 and 48 hours. No recurrences or symptoms were reported at one-month follow-up. Results: Patients who underwent minimally invasive and robotic surgery, despite not being exempt from complications, demonstrated benefits such as shorter hospital stay (48 hours), minimal bleeding, and efficient docking times. The use of three robotic arms reduced costs by 30%. Although meshes were not used for hiatal hernias, their potential benefits are recognized. Conclusion: Robot-assisted hiatal hernioplasty is a safe, reproducible technique with excellent postoperative results. Standardization of the procedure and training of the multidisciplinary team are fundamental to optimizing clinical outcomes. This approach represents an evolution in minimally invasive surgery and should be considered as a valid option in centers with experience in robotic surgery.